2018
DOI: 10.3892/ijmm.2018.3958
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-145-5p in cancer cells�and their�derived exosomes may contribute to�the�development of ovarian cancer by targeting CT

Abstract: The present study aimed to identify shared microRNAs (miRNAs) in ovarian cancer (OC) cells and their exosomes using microarray data (accession number GSE103708) available from the Gene Expression Omnibus database, including exosomal samples from 13 OC cell lines and 3 normal ovarian surface epithelial cell lines, and their original cell samples. Differentially expressed miRNAs (DE-miRNAs) were identified using the Linear Models for Microarray data method, and mRNA targets of DE-miRNAs were predicted using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…4 Recent evidence indicated that exosomes act as a diagnostic biomarker in lung cancer, 5 ovarian cancer, 6 and pancreatic cancer. 4 Recent evidence indicated that exosomes act as a diagnostic biomarker in lung cancer, 5 ovarian cancer, 6 and pancreatic cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recent evidence indicated that exosomes act as a diagnostic biomarker in lung cancer, 5 ovarian cancer, 6 and pancreatic cancer. 4 Recent evidence indicated that exosomes act as a diagnostic biomarker in lung cancer, 5 ovarian cancer, 6 and pancreatic cancer.…”
mentioning
confidence: 99%
“…fusion with the cell membrane. 4 Recent evidence indicated that exosomes act as a diagnostic biomarker in lung cancer, 5 ovarian cancer, 6 and pancreatic cancer. 7 Exosomes have been implicated in the tumor metastatic process to normal tissues via the transfer of cancer-specific cargo (ie, microRNA, RNAs and proteins), 8 one of which the most exciting molecular marker for tumor diagnosis is microRNA (miRNA).…”
mentioning
confidence: 99%
“…Another miRNA involved in many processes is miR–145. It participates in primordial follicle development and maintenance in mice [ 44 ], has higher expression levels in the follicular stage than the luteal stage in sheep experiments [ 45 ], or suppresses colorectal cancer cell viability and proliferation [ 46 ], but when downregulated, it enhances oocyte maturation and cell survival [ 47 ] or might serve as an ovarian cancer biomarker [ 39 , 48 ]. MiR–146 is reported to control reproductive functions by inhibiting the release of ovarian progesterone [ 49 ], whereas the downregulation of miR–146b–3p expression suppresses the proliferation and migration of cervical cancer cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of an effective molecular biomarker for diagnosing early stage ovarian cancer is a key contributor to its overall poor prognosis (27). Lastly, tissue-extracted circRNAs may not be the ideal biomarker considering that circRNAs are also stable and abundant in exosomes (28,29). The detection of circRNAs from exosomes in plasma or serum may be a better alternative in diagnosing disease.…”
Section: Discussionmentioning
confidence: 99%